Cudweed's time machine - Sedgwick,Marcus; Illustrator, Pete Williamson (London, Orion Children's Books, 2013)
Early Readers are stepping stones from picture books to reading books. A blue Early Reader is perfect for sharing and reading together. A red Early Reader is the next step on your reading journey. Cudweed comes face to face with Roman soldiers, dinosaurs and Vikings in this funny, quirky story, perfect for beginner readers, from the bestselling Raven Mysteries team, Marcus Sedgwick and Pete Williamson
A1 Shelf
Keywords: English story book